IDENTITAS NASIONAL ANAK PEKERJA MIGRAN DI SB PPWNI KLANG SELANGOR, MALAYSIA, INDONESIA, BUGIS ? - Anjani, Mutia; Yulianie, Putri; Karliani, Eli; Triyani , Triyani; Cionita , Tezara (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to understand the formation of national identity of children of Indonesian migrant workers at the Learning Center of the Representative of the Indonesian Citizens' Movement (PPWNI) Klang, Selangor, Malaysia. The research method used is descriptive qualitative, which focuses on in-depth description and interpretation of social phenomena, as well as understanding the experiences and views of the research subjects. The subjects of this study were grade III students at the PPWNI Klang Learning Center. Data were collected through participant observation, in-depth interviews, and documentation studies. The results of the study indicate that the national identity of children of Indonesian migrant workers at the PPWNI Klang guidance center tends to lead to primary identity, without ignoring secondary identity. This primary identity is manifested in pride in their ethnic origin (Bugis) and the use of the Bugis language in everyday life. Nevertheless, these children of migrant workers still show a sense of nationalism and love for the Indonesian homeland, for example by displaying the Indonesian flag juxtaposed with the Malaysian flag. This study also identifies factors that influence the formation of national identity of these children of migrant workers, amidst the complexity of the problems of their parents' residency status in Malaysia. ABSTRAKPenelitian ini bertujuan untuk memahami pembentukan identitas nasional anak pekerja migran Indonesia di Sanggar Belajar Perwakilan Pergerakan Warga Negara Indonesia (PPWNI) Klang, Selangor, Malaysia. Metode penelitian yang digunakan adalah deskriptif kualitatif, yang berfokus pada pendeskripsian dan interpretasi mendalam mengenai fenomena sosial, serta pemahaman tentang pengalaman dan pandangan subjek penelitian. Subjek penelitian ini adalah siswa kelas III di Sanggar Belajar PPWNI Klang. Data dikumpulkan melalui observasi partisipan, wawancara mendalam, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa identitas nasional anak pekerja migran Indonesia di sanggar bimbingan PPWNI Klang cenderung mengarah pada identitas primer, tanpa mengesampingkan identitas sekunder. Identitas primer ini termanifestasi dalam kebanggaan terhadap suku asal (Bugis) dan penggunaan bahasa Bugis dalam keseharian. Meskipun demikian, anak-anak pekerja migran ini tetap menunjukkan rasa nasionalisme dan cinta tanah air Indonesia, misalnya melalui pemasangan bendera Indonesia yang disandingkan dengan bendera Malaysia. Penelitian ini juga mengidentifikasi faktor-faktor yang memengaruhi pembentukan identitas nasional anak-anak pekerja migran tersebut, di tengah kompleksitas permasalahan status kependudukan orang tua mereka di Malaysia.